A systematic review of the effects of sedatives and anesthetics in patients with obstructive sleep apnea - Saravanan Ankichetty; Jean Wong; Frances Chung (Wolters Kluwer Medknow Publications, 2011)
The objective of this review is to determine the effects of perioperative sedatives and anesthetics in surgical patients with obstructive sleep apnea (OSA) on respiratory events, medication requirements, hemodynamics, pain, emergence, and hospital stay. We searched The Cochrane CENTRAL Register of Controlled Trials, Medline, Embase, and Cochrane Database of Systematic Reviews from 1950 to June 2010 for relevant articles. All prospective and retrospective studies were eligible for inclusion if the effects of perioperative administration of sedation and anesthetics on medication requirements, pain, emergence, hemodynamics, respiratory events, and length of hospital stay in OSA patients were reported. T0 he search strategy yielded 18 studies of 1467 patients. Of these, 456 patients were documented as having OSA. Few adverse respiratory effects were reported. Eight out of 700 (1.14%) patients undergoing middle ear surgery with midazolam and fentanyl had impaired upper airway patency and were retrospectively diagnosed as having OSA by polysomnography. Also, intraoperative snoring causing uvular edema in the postoperative period was described in an OSA patient undergoing upper limb surgery when propofol was administered with midazolam and fentanyl for sedation. A decrease in oxygen saturation in the postoperative period was described with propofol and isoflurane in 21 OSA patients undergoing uvulo-palato-pharyngoplasty and tonsillectomy surgery (P<0.05). Perioperative alpha 2 agonists were shown to decrease the use of anesthetics (P<0.05), analgesics (P=0.008) and anti-hypertensives (P<0.001) in OSA patients. Contradictory reports regarding emergence occurred with intraoperative dexmedetomidine. Intraoperative opioids decreased the analgesic consumption (P=0.03) and pain scores (P<0.05) in the postoperative period. There was limited data on the length of hospital stay. There were few adverse effects reported when patients with known OSA underwent elective surgery with the currently available sedatives and anesthetics. Adverse events were reported with midazolam. However, the quality and number of patients in the studies were limited. There is a need for further trials with large numbers and uniform reporting of outcomes.